2021
DOI: 10.53293/jasn.2021.3869.1049
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of V2O5 and SnO2 Nanoparticles and Their Application as Pollutant Removal

Abstract: Vanadium pentoxide and Tin dioxide nanoparticles were prepared by hydrothermal methods to remove methylene blue (MB) and bromothymol blue (BTB) dyes). First the prepared nanoparticles were heated at different temperature (90 o C and 500 o C). Then these nanoparticles were characterized by different methods such as UV/Visible, FT-IR Spectroscopy, X-Ray Diffraction (XRD), Atomic Force Microscopy (AFM), and Scanning Electron Microscopy (SEM). Our results explain that vanadium pentoxide nanoparticles appeared high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…In addition to energy storage, vanadium pentoxide is used in environmental cleanup. Research has shown its efficacy in removing pollutants, particularly in breaking down organic dyes, highlighting its promise for water treatment [11]. Vanadium pentoxide nanoparticles have been studied for their catalytic characteristics in detecting hydrazine, showing promise for use in sensing applications [12].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to energy storage, vanadium pentoxide is used in environmental cleanup. Research has shown its efficacy in removing pollutants, particularly in breaking down organic dyes, highlighting its promise for water treatment [11]. Vanadium pentoxide nanoparticles have been studied for their catalytic characteristics in detecting hydrazine, showing promise for use in sensing applications [12].…”
Section: Introductionmentioning
confidence: 99%